A capacity recoverable zinc-ion micro-supercapacitor. Issue 12 (5th November 2018) - Sun, Guoqiang; Yang, Hongsheng; Zhang, Guofeng; Gao, Jian; Jin, Xuting; Zhao, Yang; Jiang, Lan; Qu, Liangti
Abstract : A capacity-recoverable zinc-ion micro-supercapacitor with high energy and power density is developed. Abstract : To achieve high energy and power density simultaneously in miniaturized electronic devices, a zinc-ion micro-supercapacitor (ZmSC) is constructed for the first time by integrating a battery-type zinc micro-anode and a capacitor-type carbon nanotube micro-cathode. In the meantime, an electroplating method is developed to in situ replenish the zinc anode when needed without destroying the configuration of the ZmSC, in which the micro-cathode, micro-anode and electrolyte of the ZmSC function as the working electrode, counter electrode and plating solution in the plating process, respectively. This strategy effectively avoids the irreversible consumption of the zinc anode and the fading of the capacitance and cycle life. As a result, the prepared ZmSC exhibits an excellent electrochemical performance, including a high area capacitance of 83.2 mF cm −2 at 1 mA cm −2, a high energy density of 29.6 μW h cm −2 and a high power density of 8 mW cm −2 . After 6000 cycles, the ZmSC shows about 87.4% retention (60.9 mF cm −2 ) of its initial area capacitance at 5 mA cm −2 . Furthermore, a higher capacitance (76 mF cm −2 ) and a longer cycling life are obtained after re-plating the zinc anode. This method features a simple configuration and easy operation, and holds great promise for use in other long cycle life zinc-based microdevices.